EFFICACY OF GUDA AMALKI YOGA IN PITTAJ MUTRAKRUCCHA WSR CYSTITIS – A REVIEW STUDY - Dupade, Vaishali Uday; Narhare, Laxmi M (International Journal of Research -GRANTHAALAYAH, 2022)
According to Ayurved, dosh, dhatu, mala are basic elements of human body. When they cross their normal limit i.e kshaya and vruddhi then disease starts to occur. In normal opd it is seen that pittaj Mutrakruccha is common disease. Modern lifestyle is responsible for such disease. Shoolyukta, Raktayukta, Dahayukta and muhurmur mutraPrawrutti is symptoms of pittaj Mutrakruccha. In modern, it can compare with cystitis. Burning micturition, dysuria, increases frequency of urination are main symptoms of cystitis. There are plenty of antibiotic and other medicines are available for that but it’s seen that, there is resistance comes for this medicine. There is description of Guda Amalaki Yoga in chakrdutta. Its simple ayurvedic formulation. As per it’s contain its useful drug on pittaj Mutrakruccha. It’s my review study which theoretically proves that efficacy of Guda Amalaki Yoga in pittaj Mutrakruccha.